Effect of a family heart health program on stage of change constructs of exercise and leisure time exercise in family members of patients with heart disease - Kocourek, Jana (University of Ottawa (Canada), 2009)
The purpose of this study was to assess the effect of a family heart health program on stage of change constructs for exercise behaviour and self-reported leisure time exercise in family members of patients with coronary heart disease (CHD). One hundred and thirty eight participants were recruited by mailing an invitation to family members of patients with CHD enrolled in a cardiac rehabilitation program. Siblings, offspring and spouses of patients were eligible to participate if they did not have existing CHD or disease equivalent (diabetes, peripheral vascular disease and/or cerebro-vascular disease). Participants completed an individualized coronary risk factor assessment followed by an hour-long stage-matched counseling session with a health educator. Outcomes measures included stage of change constructs for exercise behaviour (readiness to change, decisional balance, processes of change and self-efficacy) as well as self-reported leisure time exercise. Outcomes were assessed at baseline, immediately after the counseling session, and three months later. Complete follow up data was obtained for 73 participants. Data were found to be missing completely at random and complete case analysis was used. Compared to baseline, the proportion of participants in the combined action/maintenance stage increased from 50.7% to 78.1.% at three month follow-up (p = 0.02). Decisional balance was higher at three-month follow-up than at baseline (-1.43 vs. -2.52; p < .0001), and higher at three-month follow-up than at post-intervention (-1.43 vs. -2.43; p < .0001). There was a significant difference in the scores for total processes of change at three-month follow-up (M =3.39, SD =0.59) compared to baseline (M = 3.21, SD =0.62); t (72) = -2.73, p = .008. Participants were using more processes of change at follow-up, including both cognitive and behavioural processes. There were no significant changes in mean self-efficacy between the three time points. There was a significant increase in reported exercise minutes per week at three-month follow-up (M = 268.9 minutes, SD = 262.3) compared to baseline (M = 178.8 minutes, SD = 153.8); t (73) = -2.12, p = .040. Participation in a family heart health program was associated with favourable changes in readiness to change exercise behaviour, decisional balance, use of processes of change, and self-reported leisure time exercise over a three-month follow-up period. The results of the study should be interpreted with caution given limitations with the study design and the self-reported nature of the interventions. Nonetheless, this study has set the stage for a larger, definitive trial of an enhanced family heart health intervention. This trial is now underway at the UOHI.
Keywords: Health Sciences, Public Health.; Health Sciences, Recreation.